A study on effective learning of novice programmer among engineering students at UiTM Cawangan Pulau Pinang / Azlina Mydin, Wan Anisha Wan Mohammad and Syarifah Adilah Mohamed Yusoff - Mydin, Azlina; Wan Mohammad, Wan Anisha; Mohamed Yusoff, Syarifah Adilah (Universiti Teknologi MARA, Kedah, 2019)
Learning is a process of seeking knowledge in a very creative way. The process varies among students. Different subjects have different techniques in learning. This study will identify the suitability of learning styles focusing on programming subject for novice users. We choose the most established learning model, which is VARK Model to find the best approach on students' learning styles. VARK stands for Visual (V), Aural (A), Read/Write (R), and Kinaesthetic (K). We concentrate on three learning styles, which are Visual, Auditory, and Kinaesthetic, and on how it influences student's enthusiasm in learning programming. The results show that the students prefer active learning that involves face-to-face interaction in order to understand the programming course across the three mentioned learning styles. Hence, this creates significant challenge to apply blended learning method in this course